Penilaian Afektif Guru pada Siswa dalam Pembelajaran Pendidikan Kewarganegaraan di Sekolah Dasar - Ramadhani, Nurul; Shaleh, Shaleh (Program Studi Pendidikan Guru Madrasah Ibtidaiyah (PGMI) Fakultas Tarbiyah dan Ilmu Keguruan (FTIK) Institut Agama Islam Tarbiyatut Tholabah (IAI TABAH) Lamongan, 2024)
This study aims to examine how teachers apply affective assessment to civic education learning in Taloko Public Elementary Schools. The purpose of the researcher is to evaluate (1) how teachers apply affective assessment of civics subjects in elementary schools, and (2) how future challenges related to affective assessment of PKn learning (3) how teachers relate affective values to PKn learning. The research method used by researchers is qualitative research that can be used to analyze people's lives, history, behavior, performance management, social movements or kinship. The results of research that has been carried out at SDN Taloko, Sanggar District, Bima Regency regarding how teachers apply affective assessment to civic education learning in elementary schools can be concluded that teachers apply affective assessment to Civics learning, namely Making questionnaires & rubrics, discussions and reflections, using lessons or stories, using Collaborative Activities, involving students in role play or role-play, Observation and assessment. By applying these various methods, teachers can more easily apply affective assessment which aims to develop students' impact on PKn learning. Affective values have a very important role in learning Civic Education (PKn). Because PKn is not only concerned with knowledge and skills, but also shapes attitudes, values, and awareness of responsible citizens. By connecting affective values into PKn learning, teachers can help shape students who can become responsible, caring, and active citizens in building a better community life.